Historical truth historical criticism and ideology : Chinese historiography and historical culture from a new comparative perspective - Schmidt-Glintzer, Helwig; Mittag, Achim, 1958-; Rüsen, Jörn (Leiden series in comparative historiography, 2005)
The first comprehensive work on the political and cognitive dimensions of Chinese historical consciousness set against its Western counterpart.